The Joint Influence of Ethical Human Resource Practice, Ethical Investor Relations, Ethical Consumer Relations and Ethical Advertising on the Financial Performance of Listed Firms in Kenya. - Ogwoka, Manduku Daniel; Namada, Dr. Juliana; Sikalieh, Dr. Damary (Human Resource and Leadership Journal, 2017)
Purpose: The general objective of this study was to establish the joint influence of ethical human resource practice, ethical investor relations, ethical consumer relations and ethical advertising on the financial performance of listed firms in Kenya. Methodology: Primary data was collected through a semi-structured questionnaire. Secondary data was collected from both the listed firms in the Nairobi Securities Exchange (NSE), and information from the sector regulator, the Capital Markets Authority (CMA). The target population of this study was 64 companies listed in the Nairobi Securities Exchange (NSE) with consistency being evaluated between the years 2011 to 2015. Data analysis was done using the Statistical Package for Social Scientists (SPSS). Results: The study did a joint regression test for the combined effects of ethical human resource practices, ethical advertising practices, ethical consumer practices and ethical relation practices. In the regression, it was established that, acting jointly, these practices have a positive relationship with the financial performance of listed firms. Unique contribution to theory, practice and policy: This study recommends that listed firms need to religiously adhere to conducts of ethical leadership. The departments of human resource should at all times implement their human resource policies with great caution as their mandates, as outlined in the HR policy, influence their organizational performance. The marketing departments should uphold zero tolerance to unethical advertising practices. Also, a feedback platform needs to be included in all advertisements so that profitability is achieved. To the consumers, quality is of priority. Listed firms should formulate ways of always adhering to provision of quality services to consumers. On ethical investor relations, there is need to involve truthful disclosure of information, especially regarding financial statements of the firms. Truthful disclosure of information will uphold investor trust, and subsequently inject more incentives (majorly in the form of financial) for the benefit of the firms. Overally, the study recommends that, by practicing ethical leadership, the firms' financial performance will greatly improve. The study also suggested that ethical leadership practices should be replicated in non-listed firms and in government agencies.